Training on Utilizing AI-Based Learning Analytics from Digital Assessment Data to Design Effective Mathematics Learning Interventions - Sundayana, Rostina; Muthmainnah, Maulidya; Puspitasari, Rista; Zahra, Salma Nur; Putri, Sari (Indonesian Journal of Community Empowerment (IJCE), 2025)
Data-driven learning is gaining increasing attention. Learning analytics, which is the measurement, collection, and analysis of data about students and their learning contexts, has significant potential to revolutionize how we understand and improve the teaching and learning process. This training was conducted through a systematic and structured mechanism, encompassing several stages. First, it introduced the basic concepts of learning analytics and the importance of digital assessment data. Results from the training on utilizing AI-based learning analytics to design effective mathematics learning interventions showed that participants experienced significant improvements in their understanding and skills in using digital assessment data. The use of this data, both quantitatively and qualitatively, resulted in a mapping of each student's needs and progress in understanding mathematical concepts. One important outcome was the participants' ability to design learning interventions based on data analysis. Participants demonstrated creativity in integrating analytics software to provide actionable feedback for students who needed additional support.